Estudo in vivo e in vitro do vedamento marginal em restaurações de resina composta em cavidades de classe V - Badini, Sérgio Ricardo Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2001)
The purpose of this study was to verify the marginal infiltration, in restorations of Class V, restored with composed resin and two adhesive systems, being varied the methodology type: study in vivo and in vitro. In the study in vitro, two tests was accomplished: I) thermocycling, with 300 cycles of thirty seconds each in bathing among 5ºtu 55º C and2) study in vitro being used thermocycling more load of 33kgf/100 cycles. 60 higidhuman bicuspids were used, where cavity of Class Vwere made with dimensionsof approximately 3mm of widthX 2mm of height X2mmof depth. The teeth for the tests in vitro were handomlydivided in four groups of ten teeth each: a) group 1- load application and thermocycling with the employment of adhesive Single Bond; b) group 2- load application and thermocyclingwith the employment of the Pime&Bond NT; c) group 3- thermocyclingapplication with the employment of adhesive Single Bond; d) group4 - thermocycIingapplication with the employment of the Prime &Bond NT. Theteeth were colored with fingernail enamel, being respected distances if of 1mm of the restoration, they were immerged in solution of silver nitrate at 50% for 24 hours, washed and dryand exposed to the fluorescent light by eight hows indeveloping solution Kodak. After that period, the teeth received two cuts in oclusogengival sense, to verify the infiltration in stereomicroscopy. For the studies in vivo, they were formed twogroups: e) group 5 - application of the adhesive system Single Bond; f) group 6 - applicationof the adhesive systemPrime &Bond NT. After the restorations complete, the twenty teeth stayed in function by sixty days. They were extracted, clean and painted with fingernail enamel, being respected distances it of 1mm ofthe restoration, they were immerged in solution of silver nitrate at 50% for 24hours, washed and dry and exposed to the fluorescentlight by eight hours in developing solution Koda...

A finalidade deste trabalho foi verificar a possível infiltração marginal, em cavidades de Classe V, restauradas com resina composta e dois sistemas adesivos, variando-se o tipo de metodologia: estudo in vivo e in vitro. No estudo in vitro,foram realizados dois testes laboratoriais: 1) termociclagem, empregando-se 300 ciclos de trinta segundos cada em banhos entre 5a 55 C e, 2)utilizando-se termociclagemmais carga de 33kgf/cem ciclos. Foram utilizadas 60 pré-molares humanoshigidos, onde foram confeccionados preparos cavitários de Classe V com dimensões de aproximadamente 2mm de largura X 2mm de altura X 1,5rnmde profundidade. Os dentes para os testes in vitroforam aleatoriamente divididosem quatro grupos de dez dentes cada: grupo 1 - aplicação de carga etermociclagem com o emprego do adesivo Single Bond; grupo 2 - aplicação decarga e termociclagem com o emprego do adesivo Prime & Bond NT; grupo 3 -aplicação de termociclagem com o emprego do adesivo Single Bond; grupo 4 -aplicação de termociclagem com o emprego do adesivo Prime & Bond NT. Osdentes foram pintados com esmalte de unha, respeitando-se a distancia de 1 mm darestauração, ficaram imersos em solução de nitrato de prata a 50% por 24 horas,lavados e secos e expostos a luz fluorescente por oito horas em solução reveladora Kodak. Apos esse período, os dentes receberam duas secções no sentido oclusogengival, para verificar a infiltração em estereomicroscópio. Para os estudos invivo, formaram-se dois grupos: grupo 5 - aplicação do sistema adesivo SingleBond; grupo 6 - aplicação do sistema adesivo Prime & Bond NT. Apos os vinte edois dentes terem sido restaurados e permanecidos em função por sessenta dias, osmesmos foram extraídos, limpos e pintados com esmalte de unha, respeitando-se a distancia de 1 mm da restauração, ficaram imersos em solução de nitrato de prata a50% por 24 horas, lavados e secos e ...
Keywords: Resinas compostas; Adesivos dentarios; Cavidade dentaria - Preparo; Composite Resins